The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1590/s1516-35982005000600040
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros ruminal, sangüíneo e urinário e digestibilidade de nutrientes em novilhas leiteiras recebendo diferentes níveis de monensina

Abstract: RESUMO -Objetivou-se verificar a influência da inclusão de diferentes níveis do ionóforo monensina sódica na dieta sobre os parâmetros ruminal, sangüíneo e urinário e a digestibilidade aparente em novilhas leiteiras. Foram coletadas amostras de líquido ruminal (imediatamente antes e duas horas após a alimentação), sangue, urina e fezes de 28 novilhas da raça Holandesa mantidas em regime de confinamento por 84 dias. As dietas possuíam 32,84% de concentrado (grão de milho, farelo de soja, uréia e mistura mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
2
1
0
3
Order By: Relevance
“…The present experiment showed that the use of monensin at 18 mg kg −1 of DM does not influence changes in DMI and nutrient intake nor in digestibility, as shown by other studies (Oliveira et al, 2005;Fonseca et al, 2016). This fact is attributed to the action of monensin in altering the proportion of rumen microorganisms, and consequently, the proportion of short-chain fatty acids (SCFA) and byproducts (i.e., H 2 , CO 2 , CH 4 ) formed from feed fermentation (Nagaraja and Taylor, 1987), but without significantly affecting the digestion, passage rate, and feed intake (Bretschneider et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present experiment showed that the use of monensin at 18 mg kg −1 of DM does not influence changes in DMI and nutrient intake nor in digestibility, as shown by other studies (Oliveira et al, 2005;Fonseca et al, 2016). This fact is attributed to the action of monensin in altering the proportion of rumen microorganisms, and consequently, the proportion of short-chain fatty acids (SCFA) and byproducts (i.e., H 2 , CO 2 , CH 4 ) formed from feed fermentation (Nagaraja and Taylor, 1987), but without significantly affecting the digestion, passage rate, and feed intake (Bretschneider et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…This fact is attributed to the action of monensin in altering the proportion of rumen microorganisms, and consequently, the proportion of short-chain fatty acids (SCFA) and byproducts (i.e., H 2 , CO 2 , CH 4 ) formed from feed fermentation (Nagaraja and Taylor, 1987), but without significantly affecting the digestion, passage rate, and feed intake (Bretschneider et al, 2008). Similar results were reported by other authors in bulls (Fonseca et al, 2016) and Holstein cows in lactation (Eifert et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As amostras de conteúdo ruminal foram colhidas no 24º dia de cada período experimental e os procedimentos de coleta e as medições de pH foram feitos como descrito por Oliveira et al (2005). Ao final do ensaio, foram feitos pools do líquido ruminal das vacas em cada T e dos diferentes períodos, para se mensurarem os ácidos graxos voláteis (AGV) e o nitrogênio amoniacal (N-NH³) no rúmen.…”
Section: Methodsunclassified
“…PUBVET, Londrina, V. 2, N. 43, Art#414, Out5, 2008. tampões e das leveduras, que tem seu uso mais amplo na bovinocultura de leite e em sistemas de produção que utilizam dietas ricas em grãos. Outros ainda, estão em fase de pesquisa, exemplos seria o lipídeo e a própolis, utilizados como manipuladores ruminais (Oliveira, 2005).…”
Section: Introductionunclassified